Efficacy and prognostic factors of treatment retention with intravenous abatacept for rheumatoid arthritis: 24-month results from an international, prospective, real-world study - Nüßlein, Hubert G.; Lorenz, Hanns-Martin (Clinical and experimental rheumatology, 2016)
Objectives: - To evaluate retention of abatacept over 24 months in patients with rheumatoid arthritis (RA) in routine clinical practice across Europe and Canada. - - Methods: - ACTION (AbataCepT In rOutiNe clinical practice) was a prospective, observational, multicentre study of adult patients with moderate-to-severe RA who, at their physician's discretion, initiated treatment with intravenous abatacept. Enrolment occurred from May 2008 to December 2010, with up to 30 months of follow-up. The primary endpoint was the abatacept retention rate over 24 months. Crude abatacept retention rate was estimated using the Kaplan-Meier method. Prognostic factors of abatacept retention in patients with ≥1 prior biologic failure were derived from a Cox proportional hazards regression model, accounting for clustered data. - - Results: - A total of 1137 patients were enrolled (1573 patient-years on abatacept); most (89.2%) had experienced prior biologic failure. The overall crude abatacept retention rate at 24 months was 54.4% (95% confidence interval: 51.3, 57.4). Positivity for both rheumatoid factor and anti-cyclic citrullinated antibody, previous exposure to one or no anti-tumour necrosis factor agents, and cardiovascular comorbidity were prognostic of higher abatacept retention. Erythrocyte sedimentation rate ≥51 mm/hour and introduction of corticosteroid use at abatacept initiation were predictors of lower abatacept retention. Abatacept retention varied according to country. Abatacept was well tolerated without any unexpected safety signals. - - Conclusions: - In a real-world setting, intravenous abatacept treatment retention was more than 50% at 24 months. The identification of prognostic factors of abatacept retention could support individualised biologic treatment strategies in patients with moderate-to-severe RA.
Gesehen am 17.09.2019